Biogeographical evidence suggests a Panama–Northwest South American origin for Dryadella (Orchidaceae: Pleurothallidinae) and two independent lineages of Atlantic Rainforest endemics - Mauad, Anna Victoria S R; Imig, Daniela Cristina [UNESP]; Da Silva-Pereira, Viviane; De Brito, Antonio L V Toscano; De Camargo Smidt, Eric [UNESP] (Oxford University Press (OUP), 2025)
Abstract Dryadella is a small genus distributed from Central America through the Andes to Southeastern Brazil, with a disjunct distribution between coastal forests. Despite its wide and discontinuous range, the genus exhibits remarkable morphological similarity among species. Therefore, we inferred a phylogenetic tree based on a representative sample of the genus, as well as molecular dating and biogeographical analyses to explore the evolutionary history of the genus across time and space. The findings strongly support the monophyletic origin of Dryadella, which occurred in the Late Miocene to Early Pliocene in the Pacific dominion. We found three main clades within the genus with no diagnostic morphological characteristics, which originated during the Pliocene, aligning with significant dispersal events among the northern bioregions. We observed two vicariance events, one at the Pliocene and the other at the Pleistocene, that led to two independent lineages in the Atlantic Rainforest, which diversified in situ during the Quaternary. Therefore, the lack of morphological identity and the strong geographical component of the clades suggest the genus is a recent lineage still differentiating and subject to local selective pressures. Moreover, the biogeographical evidence reinforces hypotheses of ancient connections between the tropical forests of South America and suggests that forest discontinuity could be an important driver of endemism in the genus.